2017
DOI: 10.1016/j.celrep.2017.09.089
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipid Homeostasis Regulates Dendrite Morphogenesis in Drosophila Sensory Neurons

Abstract: Summary Disruptions in lipid homeostasis have been observed in many neurodevelopmental disorders that are associated with dendrite morphogenesis defects. However, the molecular mechanisms of how lipid homeostasis affects dendrite morphogenesis are unclear. We find that easily shocked (eas), which encodes a kinase with a critical role in phospholipid phosphatidylethanolamine (PE) synthesis, and two other enzymes in this synthesis pathway are required cell-autonomously in sensory neurons for dendrite growth and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 36 publications
0
36
0
Order By: Relevance
“…Taken together, our studies provide in vivo evidence for the activity-dependent transcriptional regulation of neuronal lipo-protein receptors, a mechanism for augmenting the capacity of lipoprotein uptake in response to alterations of synaptic activity. Given the importance of lipid homeostasis in the development and maintenance of neuronal structure and function, as well as the evolutionarily conserved molecular machinery involved in its regulation ( Bailey et al, 2015 ; Meltzer et al, 2017 ; Welte, 2015 ), our findings provide a set of molecular targets for studies related to neuronal adaptive responses and have important implications in both neural development and neurodegeneration.…”
Section: Introductionmentioning
confidence: 93%
“…Taken together, our studies provide in vivo evidence for the activity-dependent transcriptional regulation of neuronal lipo-protein receptors, a mechanism for augmenting the capacity of lipoprotein uptake in response to alterations of synaptic activity. Given the importance of lipid homeostasis in the development and maintenance of neuronal structure and function, as well as the evolutionarily conserved molecular machinery involved in its regulation ( Bailey et al, 2015 ; Meltzer et al, 2017 ; Welte, 2015 ), our findings provide a set of molecular targets for studies related to neuronal adaptive responses and have important implications in both neural development and neurodegeneration.…”
Section: Introductionmentioning
confidence: 93%
“…Accordingly, metabolic pathways of TAG are not independent from the effects of the presence of structural lipids such as glycerophospholipids or sphingolipids, which may interact with TAG metabolism at multiple levels. A prominent example of this interconnection is the repression of SREBP activity by the major Drosophila membrane lipid PE, which leads to tissue-autonomous or global alterations in de novo lipogenesis and TAG storage (Lim et al 2011;Meltzer et al 2017;Ziegler et al 2017). Likewise, PC, the second most abundant glycerophospholipid in Drosophila membranes, has been identified as a critical modulator of TAG storage.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…In the three brain regions, we found that glycerophospholipid metabolism was down-regulated in schizophrenia microbiota recipient mice compared with healthy microbiota recipient mice. Emerging studies have demonstrated that glycerophospholipids are involved in the initiation and elongation of dendritic spines 31,32. Our findings suggest that dysbiosis of the gut microbiota may participate in the pathogenesis of schizophrenia by modulating the growth of dendritic spines.…”
Section: Discussionmentioning
confidence: 51%